2020
DOI: 10.1037/lat0000162
|View full text |Cite
|
Sign up to set email alerts
|

Family strengths and Latinx youth externalizing behavior: Modifying impacts of an adverse immigration environment.

Abstract: In recent years, the federal administration has ramped up efforts to curb and enforce immigration laws, in essence redefining how immigration, particularly in the Latinx population, is viewed and dealt with in the United States. The aim of the present study was to examine Latinx family strengths in relation to youth externalizing behavior, considering the modifying impacts of the current anti-immigration environment. Data were drawn from a study of 547 mother-adolescent dyads. Adolescents were 12.80 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
12
0
1
Order By: Relevance
“…Unlike the focus on internalizing outcomes, only four articles of the 21 discussed outcomes such as hyperactivity, impulsivity, conduct difficulties, and general externalizing problems. Low rates of rule-breaking and aggression related externalizing behaviors were reported in a sample of Latinx youth, according to Calzada et al (2020). Immigrant Latinx children separated from their mothers at the border reported higher rates of "total difficulties" (which includes externalizing problems) than children who were not separated (Maclean et al, 2019).…”
Section: Mental Health Outcomes For Latinx-externalizing Disordersmentioning
confidence: 91%
“…Unlike the focus on internalizing outcomes, only four articles of the 21 discussed outcomes such as hyperactivity, impulsivity, conduct difficulties, and general externalizing problems. Low rates of rule-breaking and aggression related externalizing behaviors were reported in a sample of Latinx youth, according to Calzada et al (2020). Immigrant Latinx children separated from their mothers at the border reported higher rates of "total difficulties" (which includes externalizing problems) than children who were not separated (Maclean et al, 2019).…”
Section: Mental Health Outcomes For Latinx-externalizing Disordersmentioning
confidence: 91%
“…Strong family ties help provide migrant children and adolescents with the emotional as well as social support they need to develop a healthy sense of self (Calzada, Roche, White, Partovi, & Little, 2020; Castro‐Salazar & Bagley, 2010; Juang et al., 2018; Zhou, 1997). Family members, particularly parents, serve as agents of socialization for migrant children by teaching them their heritage language and the meaning of cultural symbols and practices (Vélez‐Agosto et al., 2017).…”
Section: An Interdisciplinary Framework Of Adaptationmentioning
confidence: 99%
“…In addition, the finding that parent immigration stress predicted youths’ externalizing behaviors is in line with earlier research on Latino immigrant youth. Indeed, prior research has found links between exo and mesosystem stressors and youth problem behaviors among Latino immigrant youth across several destination contexts, most of which were traditional immigrant contexts that have longer histories of supporting and sustaining immigrant families (Calzada et al, 2020; Lorenzo‐Blanco et al, 2016; Martinez, 2006; Ponting et al, 2018). Thus, it appears that immigration stress experienced among parents may exert adverse effects on their youth regardless of the specific context in which such stress occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Ponting et al (2018) found that discrimination‐related stress predicted externalizing symptoms in a sample of Latino adolescents in California due to increased family conflict. Calzada et al (2020) recently found that among parents who experienced a more adverse immigration context, family factors, such as parental support, parental behavioral control, and respeto (respect), were more strongly related to youth externalizing symptoms among Latino immigrant families in the United States. These findings suggest that family dynamics between parents and their children are among the most proximal spheres of influence for youth and are vulnerable to disruption due to stress associated with the immigration process.…”
Section: Introductionmentioning
confidence: 99%